Nanometer bacterial cellulose and collagen composite material as well as preparation method and application thereof

By adding nanobacterial cellulose and metal ions to the collagen material, nanobacterial cellulose and collagen composite materials with high mechanical strength and stability are prepared, which solves the insufficient mechanical performance of collagen materials in tissue repair and reconstruction. Problem, high-performance biomaterials suitable for tissue repair and reconstruction.

CN119236185AInactive Publication Date: 2025-01-03TIAN JIN SAI LU SI SHENG WU KE JI YOU XIAN GONG SI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411776298.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Collagen materials have poor mechanical strength and stability in tissue repair and reconstruction applications, limiting their application range.

Method used

Using nanobacterial cellulose and collagen composite materials, the rheological properties are regulated by adding nanobacterial cellulose suspension to the collagen solution and adding metal ions to the collagen solution to prepare composite materials with high mechanical strength and stability.

Benefits of technology

The high mechanical strength and stability of the composite material are achieved while maintaining good biocompatibility and injectability. It is suitable for tissue repair and reconstruction applications, with excellent thermal stability and adjustable rheology performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236185A_ABST
    Figure CN119236185A_ABST
Patent Text Reader

Abstract

The invention provides a nano bacterial cellulose and collagen composite material and a preparation method and application thereof, and relates to the field of biopolymer materials, the preparation method comprises the following steps: S1, dissolving recombinant collagen in water, and stirring to prepare a completely hydrated collagen solution; s2, adding the nano bacterial cellulose suspension into the collagen solution to obtain a mixed solution, wherein the mass concentration of nano bacterial cellulose in the mixed solution is 0.1-0.5%; s3, metal ions with the mass concentration of 0.05%-0.9% are added into the mixed solution, and the nano bacterial cellulose and collagen composite material is obtained. The bacterial cellulose / collagen composite material not only has high mechanical strength and stability of bacterial cellulose, but also has biological activity and biocompatibility of collagen, and has wide application prospects in the fields of tissue engineering, wound healing, drug release and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biopolymer materials, and in particular to a nano bacterial cellulose and collagen composite material, and a preparation method and application thereof. Background Art

[0002] Collagen is the most abundant protein in the human body and is widely found in tissues such as skin, bones, and tendons. In the tissue engineering application of biomaterials, collagen is generally considered to be a safe and renewable biomaterial due to its low immunogenicity. In addition, the specific amino acid sequence in collagen can promote cell adhesion and provide a suitable platform for cell growth and proliferation. However, since the triple helix structure of collagen is easily destroyed, the mechanical strength of the fibers spontaneously assembled under physiological conditions is often poor, which limits its application in tissue repair and reconstruction. Collagen has good biocompatibility and bioactivity, and can promote cell adhesion, proliferation and differentiation, so it has important applications in tissue engineering and regenerative medicine. However, when collagen is used as a scaffold material, its mechanical strength and stability are poor, which limits its scope of application.

[0003] Therefore, how to further optimize the mechanical strength and stability of collagen materials has become a technical problem that needs to be solved. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art or related technology, and provides a nano bacterial cellulose and collagen composite material and a preparation method and application thereof, which has high mechanical strength and stability as well as good biocompatibility.

[0005] The first aspect of the present invention discloses a method for preparing a composite material of nano bacterial cellulose and collagen, comprising: S1, dissolving recombinant collagen in deionized water and stirring to obtain a completely hydrated collagen solution; S2, adding a nano bacterial cellulose suspension to the collagen solution to obtain a mixed solution, wherein the mass concentration of the nano bacterial cellulose in the mixed solution is 0.1%~0.5%; S3, adding metal ions with a mass concentration of 0.05%~0.9% to the mixed solution to obtain a composite material of nano bacterial cellulose and collagen.

[0006] In this technical solution, the preparation method of the composite material of nano bacterial cellulose and collagen is optimized, the ratio of each component is precise, and its rheological properties are regulated by ion addition. The specific preparation method of the nano bacterial cellulose (Bacterialnanocellulose, BNC) used has been fully disclosed in Patent ZL202410678111.1.

[0007] According to the method for preparing the nano bacterial cellulose and collagen composite material provided by the present invention, preferably, the metal ions include monovalent metal ions, divalent metal ions and trivalent metal ions.

[0008] According to the method for preparing the nano bacterial cellulose and collagen composite material provided by the present invention, preferably, the metal ions are one or more of potassium ions, calcium ions, sodium ions, magnesium ions, and iron ions.

[0009] According to the method for preparing the nano bacterial cellulose and collagen composite material provided by the present invention, preferably, the mass concentration of the recombinant collagen in the collagen solution is 0.2%.

[0010] According to the method for preparing the nano bacterial cellulose and collagen composite material provided by the present invention, preferably, the mass concentration of the bacterial cellulose in the bacterial cellulose suspension is 1%; and the mass concentration of the bacterial cellulose in the mixed solution is 0.1%, 0.3% or 0.5%.

[0011] According to the method for preparing the nano bacterial cellulose and collagen composite material provided by the present invention, preferably, the mass concentration of metal ions in the nano bacterial cellulose and collagen composite material is 0.05%, 0.1%, 0.3% or 0.9%.

[0012] According to the method for preparing the nano bacterial cellulose and collagen composite material provided by the present invention, preferably, in step S1, the recombinant collagen powder is dissolved in deionized water at 25° C. and stirred for 30 minutes to ensure that the collagen is completely hydrated to obtain a collagen solution.

[0013] According to the method for preparing the nano bacterial cellulose and collagen composite material provided by the present invention, preferably, the nano bacterial cellulose is phosphorylated nano bacterial cellulose.

[0014] The second aspect of the present invention further discloses a nano bacterial cellulose and collagen composite material, which is prepared according to the preparation method of the nano bacterial cellulose and collagen composite material disclosed in any of the above technical solutions.

[0015] The third aspect of the present invention also discloses that the nanobacterial cellulose and collagen composite material provided by the above technical solution can be used for tissue repair and tissue reconstruction, and the nanobacterial cellulose and collagen composite material provided by the above technical solution can be used as a tissue repair material and tissue reconstruction material, or as the main component of a tissue repair / reconstruction material.

[0016] The beneficial effects achieved by the present invention include at least: using bacterial cellulose and recombinant collagen, natural products obtained by microbial fermentation, as main components, a composite material with high mechanical strength and stability, as well as good biocompatibility and injectability is prepared, which can meet the application requirements in tissue repair, reconstruction, etc. Compared with the prior art, the composite material prepared by the present invention combines the advantages of nano bacterial cellulose and recombinant collagen, has excellent thermal stability, and its rheological properties can be regulated by ion addition, which can meet the needs of different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The figure shows a schematic flow chart of a method for preparing a composite material of nano bacterial cellulose and collagen according to an embodiment of the present invention.

[0018] Figure 2 A schematic diagram showing the temperature resistance test results of the nano bacterial cellulose and collagen composite material according to an embodiment of the present invention is shown. DETAILED DESCRIPTION

[0019] In order to more clearly understand the above-mentioned objects, features and advantages of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0020] Example 1

[0021] According to one embodiment of the present invention, a composite material of nano bacterial cellulose and collagen is disclosed, comprising: 0.1-0.5% nano bacterial cellulose, 0.2% recombinant collagen, and 0.05-0.9% other cationic components in mass concentration.

[0022] In this embodiment, the specific preparation method of nano bacterial cellulose (Bacterial nanocellulose, BNC) has been fully disclosed in patent ZL202410678111.1. The composite material of nano bacterial cellulose and collagen combines the advantages of both. It not only has the high mechanical strength and stability of bacterial cellulose, but also has the biological activity and biocompatibility of collagen. This composite material has broad application prospects in the fields of tissue engineering, wound healing, drug release, etc. It not only provides a new type of scaffold material for tissue engineering and regenerative medicine, but also opens up a new direction for the research and application of biomedical materials. By continuously optimizing the preparation process and modification method, the performance of this composite material can be further improved to meet the needs of different application fields.

[0023] Example 2

[0024] like Figure 1As shown, another embodiment of the present invention also discloses a method for preparing a composite material of nano bacterial cellulose and collagen, comprising:

[0025] S1, preparing a collagen solution: dissolving recombinant collagen powder in deionized water at 25° C. and stirring for 30 min to ensure complete hydration to obtain a collagen solution;

[0026] S2, adding nanobacterial cellulose suspension: adding different proportions of nanobacterial cellulose suspension (1%, w / w) to the collagen solution to obtain different nanobacterial cellulose concentrations in the final composite material;

[0027] S3, adding cations: adding different types and concentrations of ions to the composite material of nanobacterial cellulose and collagen can further regulate its rheological properties and obtain composite materials with different properties.

[0028] Example 3

[0029] According to another embodiment of the present invention, a more detailed method for preparing the composite material of nano bacterial cellulose and collagen is disclosed, and the rheological properties of the composite material are tested:

[0030] First, the recombinant collagen powder was dissolved in deionized water at a controlled temperature (25°C) and stirred for 30 min to ensure complete hydration to obtain a collagen solution (2 g / l). Then, different proportions of nanobacterial cellulose suspension (1%, w / w) were added to the collagen solution to obtain different nanobacterial cellulose concentrations in the final composite material: 0.1%, 0.3% and 0.5% (w / w).

[0031] The rheological properties of the obtained nanobacterial cellulose-collagen composites (nanobacterial cellulose and collagen composites) were characterized: the rheological measurements were performed using a stress-controlled Discovery HR-2 hybrid rheometer (TA Instruments) equipped with an aluminum plate fixture (diameter, 40 mm; parallel plates; gap, 1000 μm). The viscoelastic properties of the composites were presented by complex viscosity, elastic modulus, and loss modulus, which varied with the changing frequency (0.1-100 rad / s). Using this method, it was found that with the increase of nanobacterial cellulose concentration in the nanobacterial cellulose-collagen composite, the elastic modulus and loss modulus of the composites were significantly increased, and at an addition amount of 0.5% (w / w), the elastic modulus was greater than the loss modulus, indicating that a gel was formed; at the same time, the viscosity of the composite also increased significantly with the increase of nanobacterial cellulose concentration. The test results show that the addition of nanobacterial cellulose can act as a stabilizer and suspending agent to enhance the mechanical properties of the collagen solution.

[0032] Example 4

[0033] According to yet another embodiment of the present invention, a performance testing process of a phosphorylated nanobacterial cellulose-collagen composite material is disclosed.

[0034] Phosphorylated nano bacterial cellulose was used to replace the nano bacterial cellulose in Example 3, and other components and preparation methods remained unchanged. The prepared phosphorylated nano bacterial cellulose-collagen composite material was tested for rheological properties:

[0035] Rheological measurements were performed using a stress-controlled Discovery HR-2 hybrid rheometer (TA Instruments) equipped with an aluminum plate fixture (diameter, 40 mm; parallel plates; gap, 1000 μm). The viscoelastic properties of the composites were presented by complex viscosity, elastic modulus, and loss modulus, which varied with the changing frequency (0.1-100 rad / s). Using this method, it was found that with the increase of the concentration of phosphorylated nanobacterial cellulose in the phosphorylated nanobacterial cellulose-collagen composite, the elastic modulus and loss modulus of the composite increased significantly, and at an addition amount of 0.5% (w / w), the elastic modulus was greater than the loss modulus, indicating that a gel was formed; at the same time, the viscosity of the composite also increased significantly with the increase of the nanobacterial cellulose concentration. In addition, the addition of calcium ions can further enhance the mechanical properties of the phosphorylated nanobacterial cellulose-collagen composite. The test results showed that the addition of 0.1% (w / w) calcium ions can form a gel in the composite at an addition amount of 0.3% (w / w) phosphorylated nanobacterial cellulose, and the viscosity is significantly increased.

[0036] Example 5

[0037] According to yet another embodiment of the present invention, the effects of different ions on the rheological properties of nano bacterial cellulose-collagen composite materials are disclosed.

[0038] Different ions of the same concentration (0.9%, w / w) were added to the phosphorylated nanobacterial cellulose-collagen composite material prepared in Example 4, including monovalent ions (Na+ and K+), divalent ions (Ca2+ and Mg2+) and trivalent ions (Fe3+) and rheological properties were tested. Rheological measurements were performed using a stress-controlled Discovery HR-2 hybrid rheometer (TA Instruments) equipped with an aluminum plate fixture (diameter, 40 mm; parallel plates; gap, 1000 μm). The viscoelasticity of composite materials with different ions is presented by complex viscosity, elastic modulus and loss modulus, which vary with the changing frequency (0.1-100 rad / s) and can be used to characterize the mechanical properties of the composite material. By using this method for detection, it can be found that the effects of divalent and trivalent ions are significantly better than monovalent ions, iron ions have the best effect, and sodium ions have better effects than potassium ions. After addition, the elastic modulus and loss modulus are significantly improved, and gels are formed except for potassium ions, and the viscosity is also greatly improved.

[0039] Example 6

[0040] According to yet another embodiment of the present invention, the effect of ion concentration on the rheological properties of nano bacterial cellulose-collagen composite materials is disclosed.

[0041] Different concentrations (0.05%-0.9%, w / w) of calcium ions were added to the phosphorylated nanobacterial cellulose-collagen composite material prepared in Example 4 and rheological properties were tested: the rheological measurement was performed using a stress-controlled Discovery HR-2 hybrid rheometer (TA Instruments) equipped with an aluminum plate fixture (diameter, 40 mm; parallel plate; gap, 1000 μm). The viscoelasticity of the composite material is presented by complex viscosity, elastic modulus and loss modulus, which vary with the changing frequency (0.1-100 rad / s). By using this method, it was found that the addition of calcium ions above 0.1% (w / w) can significantly improve the mechanical properties of the composite material, but with the further increase of calcium ion concentration, the elastic modulus and loss modulus will decrease, and the change in viscosity also shows the same rule, indicating that excessive ion concentration will have a negative impact on the mechanical properties of the composite material.

[0042] Example 7

[0043] like Figure 2 As shown, according to another embodiment of the present invention, the influence of different temperatures on the rheological properties of nano bacterial cellulose-collagen composite materials is disclosed.

[0044] Rheological measurements were performed using a stress-controlled Discovery HR-2 hybrid rheometer (TA Instruments) equipped with an aluminum plate fixture (diameter, 40 mm; parallel plates; gap, 1000 μm). In order to test the effect of different temperatures on the mechanical properties of nanobacterial cellulose-collagen composites, temperature sweep experiments were performed, which are presented by solid lines: elastic modulus (G′) and dashed lines: loss modulus (G″), which vary with temperature. The test results of this method are shown in Figure 2. Figure 2 As shown, within the temperature range of 25°C-80°C, the rheological properties of the nano bacterial cellulose-collagen composite material remain stable and are not affected by temperature, indicating that the composite material has excellent temperature resistance.

[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite material of nano bacterial cellulose and collagen, characterized in that: include: S1, dissolving recombinant collagen in deionized water and stirring to prepare a fully hydrated collagen solution; S2, adding the nano bacterial cellulose suspension to the collagen solution to obtain a mixed solution, wherein the mass concentration of the nano bacterial cellulose in the mixed solution is 0.1% to 0.5%; S3, adding metal ions in a mass concentration of 0.05% to 0.9% to the mixed solution to obtain a composite material of nano bacterial cellulose and collagen.

2. The method for preparing the composite material of nano bacterial cellulose and collagen according to claim 1, characterized in that: The metal ions include monovalent metal ions, divalent metal ions and trivalent metal ions.

3. The method for preparing the composite material of nano bacterial cellulose and collagen according to claim 1, characterized in that: The metal ions are one or more of potassium ions, calcium ions, sodium ions, magnesium ions, and iron ions.

4. The method for preparing the composite material of nano bacterial cellulose and collagen according to claim 1, characterized in that: The mass concentration of recombinant collagen in the collagen solution is 0.2%.

5. The method for preparing the composite material of nano bacterial cellulose and collagen according to claim 1, characterized in that: The mass concentration of bacterial cellulose in the bacterial cellulose suspension is 1%; the mass concentration of bacterial cellulose in the mixed solution is 0.1%, 0.3% or 0.5%.

6. The method for preparing the composite material of nano bacterial cellulose and collagen according to claim 1, characterized in that: The mass concentration of the metal ions in the nano bacterial cellulose and collagen composite material is 0.05%, 0.1%, 0.3% or 0.9%.

7. The method for preparing the composite material of nano bacterial cellulose and collagen according to claim 1, characterized in that: In step S1, the recombinant collagen powder is dissolved in deionized water at 25°C and stirred for 30 minutes to ensure that the collagen is completely hydrated to obtain the collagen solution.

8. The method for preparing the composite material of nano bacterial cellulose and collagen according to claim 1, characterized in that: The nano bacterial cellulose is phosphorylated nano bacterial cellulose.

9. A composite material of nano bacterial cellulose and collagen prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nano bacterial cellulose and collagen composite material according to claim 9 in tissue repair materials and tissue reconstruction materials.

Citation Information

Patent Citations

  • Preparation and application of cellulose nanocrystals (CNCs)-reinforced collagen compound substrate

    CN102886063A

  • Preparation method and application of antibacterial repair type electrostatic spinning collagen-bacterial cellulose composite nanofiber scaffold

    CN103751848A

  • Preparation method of bacterial cellulose composite collagen self-assembly material

    CN112442200A

  • Bacterial cellulose composite hydrogel and preparation method thereof

    CN116217969A